Synthesis of Construction Quality Assessment Model in Construction Industry - Omar, Roshartini; Subramaniam, Nisamini; Sarpin, Norliana; Kai Chen, Goh; Mohamed, Sulzakimin (Journal of Social Transformation and Regional Development, 2021)
The achievement of quality is an important component in every handover of a residential project. Good quality plays an important role in creating a good identity for the developer as well as fulfill customer’s satisfaction level. Thus, Malaysian developers have started to implement quality assessment in their residential projects. Quality assessment is carried out to evaluate quality of project. However, even though quality assessment is implemented in most of construction projects, it is still a struggle to reach customer’s satisfaction level due to the number of defects in their residential properties. Therefore, this research carries the objective of investigate lacking of construction quality assessment and developing a framework on quality assessment to reduce defects in residential projects. This paper review requirements on construction quality assessment models which has been proposed by different researchers. The result of this study used to develop a framework on construction quality assessment to fulfil the important indicators which should be included in a quality assessment. The significance of this study may help contractors to develop projects with less defects and quality residential project.